Efeitos da intervenção fisioterapêutica por meio do método pilates na dor lombar em gestantes: ensaio clínico randomizado - Ferreira, Letícia Rodrigues (2017)
Introduction: The preparation of the body for gestation involves physiological and anatomical adaptations; these changes can result in symptoms such as low back pain. This symptom causes a great impact on the quality of life of this population. Thus, it is essential to develop low-cost curative strategies that reduce government expenditures with the treatment of this dysfunction and promote the well-being of the pregnant woman. Objective: To verify the effects of the physiotherapeutic intervention through the Pilates method on low back pain during pregnancy. Methods: Randomized and controlled trial with parallel randomization (1: 1). Fifty primiparous pregnant women were randomly assigned to the Pilates Group - Pilates Method Exercises (n = 24) and Control Group - Traditional Physiotherapy Exercises (n = 12). The pregnant women were evaluated in two moments: before (14th and 20th gestational weeks) and after the intervention (34th and 36th gestational weeks). The outcomes evaluated were the low back pain intensity by the Visual Analogue Pain Scale, the low back pain-related disability using the Oswestry Disability Index questionnaire and the quality of life by the WOQOL-Bref questionnaire. Both groups were submitted to the group intervention twice a week with duration of 60 minutes. Results: A pregnant woman from the Pilates group and 13 pregnant women from the Control group abandoned the interventions. An increase in disability related to low back pain after the intervention was observed in both the Pilates group and the Control group. The intergroup analysis showed a higher increase in the Control Group when compared to the Pilates Group after the intervention. There were no significant differences in pain intensity. Quality of life remained good, not observing the decrease in quality of life. When correlating variables and number of sessions, a moderate negative correlation was observed between the number of sessions performed and the values of the Oswestry Disability Index questionnaire. Conclusion: The results suggest that both interventions were able to prevent poor quality of life and increase lumbar pain during the gestational period, but the pregnant women submitted to the Pilates Method presented lower functional impairment when compared to the control group. It was also observed that the higher the attendance at the sessions, the lower was the disability related to low back pain at the end of gestation.